Advancing Technology Education in Uzbekistan’s Secondary Schools: Memajukan Pendidikan Teknologi di Sekolah Menengah Uzbekistan - Qudratovna, To‘rayeva Surayyo (Pedagogia : Jurnal Pendidikan, 2025)
In the evolving global economy, integrating technology into education is essential for workforce readiness and innovation. Uzbekistan’s “Technology” curriculum in secondary education bridges theory and practice across nine subfields, including robotics, electronics, and traditional crafts. However, gaps remain in practical training, teacher development, accessibility, entrepreneurship, and sustainability. This study aims to evaluate the curriculum’s alignment with global best practices and propose targeted enhancements. Results highlight the need for improved industry partnerships, teacher training, equitable access, and sustainability-focused modules. The novelty lies in actionable strategies to modernize the curriculum, ensuring it fosters skills for the 21st-century labor market. Implications suggest the curriculum’s potential to drive workforce readiness, economic growth, and cultural preservation in Uzbekistan. Highlights: Integration of Skills: The "Technology" curriculum combines traditional crafts with modern disciplines like robotics and electronics to foster balanced education. Global Alignment: Benchmarking against global best practices highlights gaps in practical training, teacher development, and sustainability. Future Impact: Enhancing accessibility, entrepreneurship, and industry collaboration will ensure workforce readiness and economic growth. Keywords: Technology Curriculum, Vocational Education, Workforce Readiness, Practical Training